Green Synthesis of Antibacterial CuO Nanoparticles Based on the Synergy Between Cornu aspersum Snail Mucus and Ascorbic Acid - Maria Todorova; Angelina Kosateva; Ventsislava Petrova; Bogdan Ranguelov; Stela Atanasova-Vladimirova; Georgi Avdeev; Ivanka Stoycheva; Emiliya Pisareva; Anna Tomova; Lyudmila Velkova; Aleksandar Dolashki; Pavlina Dolashka (Molecules)
Many biologically active compounds have been identified in the mucus of the garden snail Cornu aspersum, which are effective in the treatment of several diseases such as cancer, ulcers, wounds, etc. The incorporation of these compounds into the green synthesis of copper nanoparticles (CuONPs-Muc) was demonstrated in our previous study. Based on the synergistic effect of two reducing agents—C. aspersum snail mucus and ascorbic acid (AsA)—on CuSO4.5H2O, which also act as stabilizers of the resulting compound, a new method for the “green” synthesis of CuONPs-Muc is presented. Using two reducing agents has several advantages, such as forming spherical nanoparticles with a diameter of about 150 nm and reducing the formation time of CuONPs-Muc to 3 h. Analyses by ultraviolet–visible spectroscopy (UV-Vis) and Fourier transform infrared spectroscopy (FT-IR) show the formation of CuONPs-Muc, composed of a mixture of copper and copper oxide. This was confirmed by scanning electron microscopy combined with energy-dispersive spectroscopy (SEM/EDS) and X-ray diffraction (XRD). Another important advantage of CuONPs obtained by the new method with two reducing agents is the stronger inhibitory effect on the bacterial growth of some Gram-positive and Gram-negative bacterial strains, compared to CuONPs-Muc prepared with only one reducing agent, i.e., a fraction of mucus with an MW > 20 kDa.